Children's Play-The Educator's Opinion - Ivana Visković; Esmeralda Sunko; Branimir Mendeš (MDPI AG, 2019)
The educator's personal role in understanding children's play is a key factor in planning organization of educational process in kindergarten. An educator´s personal paradigm is assumed to be an experiential and educational construct. This research examines the possible correlation of educators' personal paradigms (N = 291) and contextual factors in the region of Dalmatia (Croatia). A questionnaire Q-EOCP (α = 0.78) was designed for this research. Research findings suggest that most educators are reluctant to introduce information and communication technology /ICT into the educational process (M = 2.25; SD = 1.02) or work with children with disabilities (M = 2.03; SD = 1.33). There was a slightly positive correlation between the educator's professional work experience and the view that children with disabilities /CWD should be taught how to play (r = 0.35; p ≤ 0.05). Work experience is slightly negatively correlated with the opinion that natural materials encourage creative play in children more than the didactic toys (r = −0.29; p ≤ 0.05) and with the assessment of daily play in nature (r = −0.21; p ≤ 0.05). The research measured the correlation of assessments of daily play in nature and the educators' level of education (F = 3.47; p ≤ 0.05). Findings suggest that early childhood and preschool educators need additional education on children's play and the possibilities of augmentative technology.